POLA KOMUNIKASI KELOMPOK PADA KOMUNITAS DANCE COVER K-POP DALAM MENJALIN HUBUNGAN SOLIDARITAS (Studi Pada Komunitas DMC Project Bandar Lampung) - atiah zakiah (INTERCODE, 2023)
A group can be formed because it has the same vision, mission and purpose as secing that there are several members who move from one group to another, which can lead to conflict and envy among members of teh group. Based on the description above, the formulation of the problem of this study was “How was the group communication pattern of K-Pop Dance Cover Community in Establishing Solidarity Relations?”This research used descriptive qualitative method using the data from observations and interviews with 13 informants. The purpose of this study was to determine the communication patterns of K-Pop Dance Cover Community in strengthening the solidarity relations among its members.From the result of this study, it can be seen that the communication patterns of descriptive groups of K-Pop Dance Cover Community in establishing solidarity relations namely cohesiveness and kinship, solidarity and trust in the DMC create a sense of mutual need and respect within the community. Keywords:  Group Communication, Korean Wave, Community, Solidarity Relations